Light availability rather than Fe controls the magnitude of massive phytoplankton bloom in the Amundsen Sea polynyas, Antarctica. (21st April 2017) - Park, Jisoo; Kuzminov, Fedor I.; Bailleul, Benjamin; Yang, Eun Jin; Lee, SangHoon; Falkowski, Paul G.; Gorbunov, Maxim Y.
Abstract: Amundsen Sea polynyas are among the most productive, yet climate‐sensitive ecosystems in the Southern Ocean and host massive annual phytoplankton blooms. These blooms are believed to be controlled by iron fluxes from melting ice and icebergs and by intrusion of nutrient‐rich Circumpolar Deep Water, however the interplay between iron effects and other controls, such as light availability, has not yet been quantified. Here, we examine phytoplankton photophysiology in relation to Fe stress and physical forcing in two largest polynyas, Amundsen Sea Polynya (ASP) and Pine Island Polynya (PIP), using the combination of high‐resolution variable fluorescence measurements, fluorescence lifetime analysis, photosynthetic rates, and Fe‐enrichment incubations. These analyses revealed strong Fe stress in the ASP, whereas the PIP showed virtually no signatures of Fe limitation. In spite of enhanced iron availability in the PIP, chlorophyll biomass remained ∼ 30–50% lower than in the Fe‐stressed ASP. This apparent paradox would not have been observed if iron were the main control of phytoplankton bloom in the Amundsen Sea. Long‐term satellite‐based climatology records revealed that the ASP is exposed to significantly higher solar irradiance levels throughout the summer season, as compared to the PIP region, suggesting that light availability controls the magnitude of phytoplankton blooms in the Amundsen Sea. Our data suggests that higher Fe availability (e.g., due to higher melting rates of ice sheets) would not necessarily increase primary productivity in this region. Furthermore, stronger wind‐driven vertical mixing in expanding ice‐free areas may lead to reduction in light availability and productivity in the future.